2018
DOI: 10.1039/c8ja90025f
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Spectrometry Update: review of advances in elemental speciation

Abstract: This is the ninth Atomic Spectrometry Update (ASU) to focus on advances in elemental speciation and covers a period of approximately 12 months from December 2015. This ASU review deals with all aspects of the analytical atomic spectrometry speciation methods developed for: the determination of oxidation states; organometallic compounds; coordination compounds; metal and heteroatom-containing biomolecules, including metalloproteins, proteins, peptides and amino acids; and the use of metal-tagging to facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 266 publications
0
6
0
Order By: Relevance
“…This latest update adds to that from last year 1 and complements the five other annual Atomic Spectrometry Updates 2,3,4,5,6 . The interest highlighted in the 2018 elemental speciation ASU on the measurement of metal species in biological systems has continued with the publication of a book entitled 'Metallomics: The Science of Biometals,' volume 1055 in the series Advances in Experimental Medicine and Biology 7 .…”
Section: Topical Reviewsmentioning
confidence: 82%
“…This latest update adds to that from last year 1 and complements the five other annual Atomic Spectrometry Updates 2,3,4,5,6 . The interest highlighted in the 2018 elemental speciation ASU on the measurement of metal species in biological systems has continued with the publication of a book entitled 'Metallomics: The Science of Biometals,' volume 1055 in the series Advances in Experimental Medicine and Biology 7 .…”
Section: Topical Reviewsmentioning
confidence: 82%
“…Atomic spectrometry are subdivided into AFS, AAS, and AES (or OES), among which AFS is the most often used method, and represents a suitable alternative to the other atomic spectrometric and mass spectrometric techniques [151]. The direct coupling between HPLC and detectors will probably suffer from the interferences from the sample matrices.…”
Section: Detection Techniques For Speciation Analysismentioning
confidence: 99%
“…Analytical speciation methods for the determination of traces of elements in different chemical forms have become increasingly important in the most recent decades. This trend is ascribed to the increasing consciousness about the evidence that the total concentration of elements cannot provide complete information about the mobility and the impact of elements on environmental and biological systems. , From the analytical chemists’ point of view, this implies continuous efforts in the setting up and in the improvement of speciation methods which represent a still very active research field, as revealed by some recent reviews appeared in the literature. …”
mentioning
confidence: 99%
“…Even if direct methods, including spectrophotometric or voltammetric techniques, were developed for the speciation of several elements, the methods of choice for routine in-laboratory determination are commonly based on the hyphenation of separation techniques, such as ion chromatography (IC) and high-performance liquid chromatography (HPLC), with sensitive detection systems, such as atomic fluorescence spectrometry-hydride generation (AFS-HG), atomic absorption spectrometry-hydride generation (AAS-HG), and inductively coupled plasma-mass spectrometry (ICP-MS). , …”
mentioning
confidence: 99%
See 1 more Smart Citation